2020
DOI: 10.1021/acs.orglett.0c04074
|View full text |Cite
|
Sign up to set email alerts
|

An Organocatalytic Kinetic Resolution of Aziridines by Thiol Nucleophiles

Abstract: We report the first organocatalytic kinetic resolution of unactivated aziridines by sulfur nucleophiles with excellent enantioselectivity. A suitable chiral phosphoric acid was found to catalyze the intermolecular ring opening under mild conditions, furnishing a range of highly enantioenriched β-amino thioethers and aziridines, both of which are useful synthetic building blocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The alignment of the reaction axis with the empty quadrant is general to intermolecular openings of strained sp 3 -hybridized electrophiles, regardless of the nature of the nucleophile. 39,50–53 (B) Positioning the benzothiazole nucleophile perpendicular to the reaction axis, where it can engage in favorable C–H⋯π interactions 86 with the catalyst's binaphthyl backbone (see Fig. 4B and C , top).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alignment of the reaction axis with the empty quadrant is general to intermolecular openings of strained sp 3 -hybridized electrophiles, regardless of the nature of the nucleophile. 39,50–53 (B) Positioning the benzothiazole nucleophile perpendicular to the reaction axis, where it can engage in favorable C–H⋯π interactions 86 with the catalyst's binaphthyl backbone (see Fig. 4B and C , top).…”
Section: Resultsmentioning
confidence: 99%
“…DFT studies of similar systems have consistently shown that ring substituents preferentially point away from the catalyst. 39,[50][51][52][53] As explained above, these features could only be identied by considering all of the available arrangements of the TS leading to the minor product (Fig. 6), and not from direct comparison of the lowest-energy structures (Fig.…”
Section: Model Of Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, Huang and Sun et al reported the kinetic resolution of aziridines via CPA-catalyzed asymmetric addition with thiols (Scheme 21). [32] The KR reaction between a series of racemic aziridines 56 and 2-mercaptobenzothiazole 57 under the catalysis of CPA-13 in chloroform at 0 °C proceeded smoothly to give the recovered aziridines (S)-56 and the β-amino thioether (S)-58 with high enantioselectivities. Both aryl-and alkyl-substituted aziridines were compatible with the optimal conditions, albeit the alkyl-substituted aziridines gave relatively low s factors.…”
Section: Kinetic Resolution Of Epoxides and Aziridinesmentioning
confidence: 99%
“…The resulting eponymous Goodman model 22,33 is the gold standard in CPA catalysis, and similar models for other reaction types are highly desirable. One class of reactions that is understudied and that would benefit from improved understanding is the desymmetrization of aziridines, [34][35][36][37][38][39] epoxides, [40][41][42] azetidines, 43 and oxetanes [44][45][46][47][48][49] by ring-opening with nucleophiles. For such sp 3 -hybridized carbon electrophiles, fewer experimental reports are known.…”
Section: Introductionmentioning
confidence: 99%